The bookseller's promise - Wiseman, Beth, 1962- (Wiseman, Beth, 1962- Amish bookstore novel., 2022)
Yvonne Wilson has made the trek from Texas to Indiana to convince Amishman Jake Lantz to sell her client a rare book from his collection. But Jake had made a vow to his dying grandfather to never sell the book and he intends to keep that promise. Eva Graber has loved Jake since he hired her to work in his bookstore two years ago. When Yvonne shows up and seems like she might turn Jake's eye, Eva suggests that she and Jake read the book together. What happens afterwords surprises them all as the book leads the trio into mysterious questions about life, death, and the impenetrable purposes of God.